Impact of Digital Transformation and Big Data Analytic Capabilities of The Indonesian Bank Profitability - Muhammad Ananda Putra (Universitas Hayam Wuruk Perbanas, 2022)
This study analyzed the impact of digital transformation (DT) and big data analytic capabilities (BDAC) on bank profitability, which is proxied by ROA and ROE. This study also examined the moderation effect of institutional ownership on digital transformation (DT) relationships on bank profitability. This research uses a quantitative approach with a panel data model. The sample of this study was 34 banks listed on the Indonesian Stock Exchange from 2018 to 2021, with a total observation of 136 firm years. This research uses secondary data derived from annual reports and company financial reports. This study shows that big data analytic capabilities have no significant effect on bank profitability, which means that the impact of the application of technology is not immediately visible. This study shows that digital transformation decreased the company’s profitability. Institutional ownership failed to moderate the relationship between digital transformation on bank profitability. This finding implies the importance of companies being careful in investing in digital transformation and big data analytics because the costs outweigh the benefits in the short term.